The impact of dictogloss and blogging on EFL students’ writing skills in an Indonesian tertiary vocational college - Sri Hardiningsih; Elizabeth Anggraeni Amalo (UNIB Press, 2023)
The purpose of this study is to assess students' writing abilities using dictogloss and blogging. It involved 24 students from vocational colleges and incorporated five audio scripts from Hughes and Naunton's